Peningkatan Tren Bunuh Diri Pada Kalangan Remaja Sejak Pandemi COVID-19 di Jepang (2020-2023) - Shecilia Kriestyaning; Putri Elsy (Universitas Airlangga, 2025)
This study aims to examine the increasing trend of suicide among Japanese teenagers since the COVID-19 pandemic. The COVID-19 pandemic has had a significant impact on the mental health of people around the world, including Japan. According to data from the National Police Agency of Japan, the number of youth suicides (aged 15-19) in Japan remains at a record high and is showing an alarming trend. Contributing factors include school problems, health problems, and family problems. To analyse this phenomenon, this study uses Emile Durkheim's suicide theory approach, which classifies suicide into four types, namely egoistic, altruistic, fatalistic, and anomic. This research uses a qualitative research method through a literature study approach. The results showed that the pandemic had exacerbated suicide factors, especially the anomic and fatalistic types of Durkheim's suicide theory. Academic pressure, family expectations, and Japanese cultural norms amid social isolation interact to create conditions for adolescents who are vulnerable to the pressures of these two types of suicide. The increase in suicide rates among Japanese adolescents during the COVID-19 pandemic reflects the complexity of the social and psychological crisis facing the younger generation.